Genetics of early onset Parkinson’s disease in Finland: exome sequencing and genome-wide association study - Siitonen, A (Neurobiol Aging, 2017)
Several genes and risk factors are associated with Parkinson’s disease (PD). Although many of the genetic markers belong to a common pathway, a unifying pathogenetic mechanism is yet to be found. Also, missing heritability analyses have estimated that only part of the genetic influence contributing to PD has been found. Here, we carried out whole-exome sequencing (WES) on 438 Finnish patients with early-onset PD. We also re-analyzed previous data from genome-wide association studies (GWAS) on the same cohort. Variants in the CEL gene/locus were associated with PD in both GWAS and WES analysis. Exome-wide gene-based association tests also identified the MPHOSPH10, TAS2R19 and SERPINA1 genes in the discovery dataset (p<2.5E-6). MPHOSPH10 had estimated odds ratio (OR) of 1.53 and the rs141620200 variant in SERPINA1 had OR of 1.27. We identified several candidate genes, but further investigation is required in order to determine the role of these genes in PD.